2012
DOI: 10.1111/j.1445-2197.2012.06210.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive intraperitoneal local anaesthesia: an effective method in immediate post-operative pain management and metabolic stress response in laparoscopic appendicectomy, a randomized, double-blinded, placebo-controlled study

Abstract: Pre-emptive intraperitoneal local anaesthesia in laparoscopy surgery is a safe, non-invasive procedure that can benefit patients by reducing the immediate post-operative pain intensity and metabolic stress response of the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 9 publications
2
17
1
4
Order By: Relevance
“…Our study has confirmed the early analgesic effects of intraperitoneal local ropivacaine in laparoscopic appendicectomy in an Australian population during the first 6‐h post operation. Similar outcomes have been reported by two overseas studies . Other intraperitoneal agents such as tramadol, bupivacaine and lornoxicam with positive analgesic post‐operative effects have been reported in similar randomized controlled studies …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our study has confirmed the early analgesic effects of intraperitoneal local ropivacaine in laparoscopic appendicectomy in an Australian population during the first 6‐h post operation. Similar outcomes have been reported by two overseas studies . Other intraperitoneal agents such as tramadol, bupivacaine and lornoxicam with positive analgesic post‐operative effects have been reported in similar randomized controlled studies …”
Section: Discussionsupporting
confidence: 85%
“…We found that patients used PCA 33% times more often in the placebo group compared to the ropivacaine group, which resulted in a 28% increase in the fentanyl per kilogram usage within the first 6 h. However, the analgesic effect of the intraperitoneal local anaesthetic was seen to taper off after the initial 6 h. The reduction in additional analgesia used from the intraperitoneal group was not as significant and prolonged as suggested by Thanapel et al . This difference may be multifactorial.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Anestezi yöntemleri de cerrahiye stres yanıtı modifiye etmek için kullanılır (7). Birçok ameliyat türünde farklı anestezi ajanları ve yöntemleri ile cerrahiye karşı oluşan stres yanıtın incelenmesi halen çe-şitli araştırmalara konu olmaktadır (8)(9)(10)(11). Bu araştırmaların çoğu abdominal cerrahi ile ilgilidir; oluşan stres yanıt cerrahinin niteliği ile de ilişkili olduğundan, anestezi yöntemleri-nin farklı cerrahi türlerinde stres yanıta etkisi araştırılmalıdır (7,11,12).…”
Section: Introductionunclassified